A methodical approach to learning three-part bagpipes from Vojvodina based on the contribution of Maxim Mudrinić - Jović Vujaković, Filip (Norma, 2024)
The paper is about the first step in acquiring the basic concepts of music, melodic and rhythmic structures through singing and playing. The purpose of this work is to show the three-part bagpipes (TPB) of Vojvodina - TPB and the way of their promotion, education and affirmation. It looks at and determines the importance of TPB and gives a methodical approach to learning to play this traditional instrument is offered. Using the method of theoretical analysis and available literature, a description of the TPB instrument was given. Then the role of Maksim Mudrinić in the education and promotion of this instrument in school and non-school institutions was presented and a methodical approach to learning to play was given. Playing on various musical instruments is one of the types of active attitude towards music, and it should be started at an early age. By introducing a new folk instrument in the teaching process, a student will, through making music, develop musical abilities like pitch, rhythm and melody. Getting acquainted with the build and the way of playing this instrument they will be able to recognize more precisely the name and type of instruments through sound patterns that make every musical instrument special.
Keywords: methods; traditional instrument; playing; tradition